Blanc Reaction of Aromatic Compounds Catalyzed by Ionic Liquids - 方岩雄 邓运泉 任清刚 黄敬平 张赛丹 黄宝华 张焜 (Chinese journal of chemical engineering, 2008)
Ionic liquids have been used as catalysts for Blanc reaction of toluene. The effects of reaction temperature, reaction time and dosage of the ionic liquid catalyst have been investigated, and the catalytic performance of different ionic liquid catalysts for toluene chloromethylation was also studied. The reaction was found to proceed under mild conditions with excellent conversion （up to 90%） in the absence of Lewis acids. The ionic liquids could be recycled and reused without loss of their catalytic activities.